Naa20, the catalytic subunit of NatB complex, contributes to hepatocellular carcinoma by regulating the LKB1-AMPK-mTOR axis - Jung, Taek-Yeol; Ryu, Jae-Eun; Jang, Mi-Mi; Lee, Soh-Yeon; Jin, Gyu-Rin; Kim, Chan-Woo; Lee, Chae-Young; Kim, Hyelee; Kim, EungHan; Park, Sera; Lee, Seonjeong; Lee, Cheolju; et al. (생화학분자생물학회, 2020)
N-alpha-acetyltransferase 20 (Naa20), which is a catalytic subunit of the N-terminal acetyltransferase B (NatB) complex, has recently been reported to be implicated in hepatocellular carcinoma (HCC) progression and autophagy, but the underlying mechanism remains unclear. Here, we report that based on bioinformatic analysis of Gene Expression Omnibus and The Cancer Genome Atlas data sets, Naa20 expression is much higher in HCC tumors than in normal tissues, promoting oncogenic properties in HCC cells. Mechanistically, Naa20 inhibits the activity of AMP-activated protein kinase (AMPK) to promote the mammalian target of rapamycin signaling pathway, which contributes to cell proliferation, as well as autophagy, through its N-terminal acetyltransferase (NAT) activity. We further show that liver kinase B1 (LKB1), a major regulator of AMPK activity, can be N-terminally acetylated by NatB in vitro, but also probably by NatB and/or other members of the NAT family in vivo, which may have a negative effect on AMPK activity through downregulation of LKB1 phosphorylation at S428. Indeed, p-LKB1 (S428) and p-AMPK levels are enhanced in Naa20-deficient cells, as well as in cells expressing the nonacetylated LKB1-MPE mutant; moreover, importantly, LKB1 deficiency reverses the molecular and cellular events driven by Naa20 knockdown. Taken together, our findings suggest that N-terminal acetylation of LKB1 by Naa20 may inhibit the LKB1-AMPK signaling pathway, which contributes to tumorigenesis and autophagy in HCC. Cancer: A switch that regulates liver tumor formation Chemical modifications convert a protein that normally acts as a tumor suppressor into a driver of liver cancer cell proliferation. Many proteins are regulated via enzymatic addition of chemical groups. Researchers led by Hyun-Seok Kim at Ewha Womans University in Seoul, South Korea, set out to characterize the function of NatB, one of N-terminal acetyltransferas family that adds acetyl chemical groups to the first amino acid on selected target proteins. They found that mutations that disable NatB inhibits growth of hepatocellular carcinoma cells. Subsequent experiments provided evidence that NatB modifies a signaling protein called LKB1, which has previously been identified as a safeguard against cancer. Loss of LKB1 modification has downstream effects that favor tumor formation. These results suggest that drugs targeting NatB function may be beneficial in certain cancer subtypes.